The Factors Affecting Foreign Direct Investment Intentions of Investors: A Case of Malaysia - Zainoddin, Amir Imran; Nin, Liya Fitrya; Badyalina, Basri; Ya’acob, Fatin Farazh (Information Management and Business Review, 2024)
Foreign direct investments (FDI) are regarded as one of the most important sources of external financing for all countries in this globalisation era. In recent years, Malaysia has only been successful in attracting a small number of foreign investors. As a result, the primary goal of this paper is to examine the factors that have attracted FDI into Malaysia from 1990 to 2020. The study investigates the relationships between FDI and the proposed explanatory variables, namely market size (GDP), trade openness (OPN), inflation rate (INF), and infrastructure (INFRA). Multiple Linear Regression (OLS) is used to examine the relationships between the variables. The Variance Inflation Factor and the Breusch Pagan Godfrey test are also analysed to discover the data collected from the World Bank Data. Findings indicate GDP and INF have a significant impact on FDI. This study has not brought any evidence of INFRA and OPN influencing FDI inflows in Malaysia. Understanding these factors is crucial for policymakers and investors to promote sustainable economic growth and attract foreign investments